Effects of Land Fragmentation on Food Security in Three Agro-ecological Zones of Embu County in Kenya - Ndirangu, Samuel N.; Mbogoh, Stephen G.; Mbatia, O. L. E. (My University, 2017)
Land fragmentation is a common agricultural phenomenon in many countries where a single large farm is subdivided into a large number of separate small land plots. This paper is based on a study that was carried out to evaluate the impact of land fragmentation on food security in three agroecological zones (AEZs) of Embu County in Kenya from January to November 2016. The study used data collected from 384 farm-households that were randomly selected from three AEZs in the Embu County, using the 4-stage cluster sampling method. The AEZs were the Sunflower-Cotton Zone, the Coffee Zone and the Tea Zone, based on the official AEZs classification system in Kenya. Household caloric acquisition method was used to compute a household food security index (HFSI) that was used to measure the household food security status. The effect of farm size on food security was evaluated using the Binary Logit Regression method. The results showed that the average number of people in a household was 3.73 in the Tea Zone, 3.59 in the Coffee Zone and 3.93 in the Sunflower Zone, and that farm size had a positive and significant effect on food securityin the Sunflower (P=.029) and Tea zones (P=.007), but not in the Coffee Zone (P=.365). Further, it was found that the minimum farm-size that could ensure the attainment of the minimum (cut-off) point for household food security (HFSI = 1) was above 2 ha in the Sunflower Zone and 0.5 ha in the Tea Zone. Based on the study findings, it is recommended that further fragmentation of farms below 0.5 ha in the Coffee and Tea zones and 2 ha in the Sunflower Zone should be discouraged to ensure sustainable food security in the study area. For the farms that are already below the minimum cut-off size for food security, measures to increase these farms’ productivities so that they can support more people per ha should be devised and implemented.
Keywords: Land fragmentation; farm size; agro-ecological zones; food security